2011
DOI: 10.1016/j.cmet.2011.08.015
|View full text |Cite
|
Sign up to set email alerts
|

Activation of the HIF Prolyl Hydroxylase by the Iron Chaperones PCBP1 and PCBP2

Abstract: SUMMARY Mammalian cells express dozens of iron-containing proteins, yet little is known about the mechanism of metal ligand incorporation. Human poly (rC) binding protein 1 (PCBP1) is an iron chaperone that binds iron and delivers it to ferritin, a cytosolic iron storage protein. We have identified the iron-dependent prolyl hydroxylases (PHDs) and asparaginyl hydroxylase (FIH1) that modify hypoxia-inducible factor α (HIFα) as targets of PCBP1. Depletion of PCBP1 or PCBP2 in cells led to loss of PHD activity, m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
160
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 186 publications
(162 citation statements)
references
References 30 publications
2
160
0
Order By: Relevance
“…Silver staining revealed an additional band (arrow in Figure 8A), which was specifically present in the pull-down from the pig cortex tissue. This band was isolated for mass spectrometry and found to contain Poly(rC)-binding protein 1 (PCBP1), a nuclear RNA-binding protein [35][36][37]. We then performed GST pull-down with an antibody to PCBP1, which confirmed that pig PCBP1, but not mouse PCBP1, bound to hSOD1 ( Figure 8B).…”
Section: Hsod1 Interacts With Pcbp1 In Pig Brainsmentioning
confidence: 83%
See 1 more Smart Citation
“…Silver staining revealed an additional band (arrow in Figure 8A), which was specifically present in the pull-down from the pig cortex tissue. This band was isolated for mass spectrometry and found to contain Poly(rC)-binding protein 1 (PCBP1), a nuclear RNA-binding protein [35][36][37]. We then performed GST pull-down with an antibody to PCBP1, which confirmed that pig PCBP1, but not mouse PCBP1, bound to hSOD1 ( Figure 8B).…”
Section: Hsod1 Interacts With Pcbp1 In Pig Brainsmentioning
confidence: 83%
“…Using GST pulldown and mass spectrometry, we identified PCBP1 as a partner for binding to hSOD1 in the pig brain, but not in mouse brain. PCBP1 is a nuclear protein and, along with PCBP-2 and hnRNPK, corresponds to the major cellular poly(rC)-binding protein and has widely diversified functions in mRNA binding and stabilization, translational activation or silencing [35,37,50], as well as iron chaperone function [36]. Since most sALS cases harbor cytoplasmic inclusions containing TDP-43, nuclear proteins that are involved in binding DNA and RNA, nuclear dysfunction and abnormal processing of DNA and RNA are thought to play a role in ALS pathogenesis [51].…”
Section: Discussionmentioning
confidence: 99%
“…Iron loading mechanisms inside the cells probably reflect those studied in vitro, even though higher level of complexity and regulation may be present; in particular the interaction and loading of ferritins with iron may be enhanced in vivo by iron chaperones such as the PCBPs that can interact with ferritin with nanomolar affinity and may deliver iron directly at the hydrophilic pores (Shi et al 2008;Leidgens et al 2013). This activity is not specific to ferritin since PCBP1 and PCBP2 also facilitate iron delivery to enzymes with mononuclear and dinuclear iron centers, deoxyhypusine hydroxylase and prolyl and asparagyl hydroxylases respectively (Nandal et al 2011;Frey et al 2014) and PCBP2 can mediate cytosolic iron distribution by interacting with the membrane transporters DMT1 and Ferroportin (Yanatori et al 2014). Further studies are needed to understand the role of these ubiquitous RNA/DNA binding proteins in the maintenance of iron homeostasis.…”
Section: Mammalian Ferritin Structurementioning
confidence: 99%
“…Recent data indicate that the answer to both questions is yes. PCBP1 and PCBP2 play a role in the metallation of the iron-dependent prolyl hydroxylases (PHDs) that regulate hypoxia-inducible factor (HIF) 1␣ (20). HIF is a heterodimeric transcription factor that activates the expression of genes involved in the response to hypoxia (21)(22)(23).…”
Section: Pcbpsmentioning
confidence: 99%